Dark Ages woodland recovery and the expansion of beech: a study of land use changes and related woodland dynamics during the Roman to Medieval transition period in northern Belgium. (2020) - Deforce, Koen; Bastiaens, Jan; Crombé, Philippe; Deschepper, Ewoud; Haneca, Kristof; Laloo, Pieter; Van Calster, Hans; Verbrugghe, Gerben; De Clercq, Wim
Abstract: The results from analyses of botanical remains (pollen, wood, charcoal, seeds) from several archaeological features excavated in Kluizen (northern Belgium) are presented. The region was largely uninhabited until the Iron Age and Roman period when a rural settlement was established, resulting in small-scale woodland clearance. The site was subsequently abandoned from c. AD 270 till the High Middle Ages. The results of the archaeological and archaeobotanical analyses provide information on changes in land use and resulting dynamics of woodland cover and composition between c. 600 BC and AD 1200, with a spatial and temporal resolution unrivalled in northern Belgium. Especially the long period of woodland regeneration following abandonment of the site around AD 270, covering the Late Roman and Early Medieval period, could be reconstructed in detail. Abandoned fields were first covered with pioneer woodland ( Salix, Corylus and Betula ), then Quercus -dominated secondary forest and finally a late-successional forest with Fagus sylvatica, Carpinus betulus and Ilex aquifolium, an evolution that took over 300 years. The results also indicate that the observed increase of Fagus during the Early Middle Ages, which was never an important element in the woodland vegetation in northern Belgium before, was related to climatic changes rather than anthropogenic factors.